Impact of COVID-19 on emergency department attendance in an Australia hospital: a parallel convergent mixed methods study. Issue 12 (30th December 2021) - Jessup, Rebecca Leigh; Bramston, C; Beauchamp, A; Gust, A; Cvetanovska, N; Cao, Y; Haywood, C; Conilione, P; Tacey, Mark; Copnell, Beverley; Mehdi, H; Alnasralah, Dialla; et al.
Abstract : Objectives: The COVID-19 pandemic has changed the way people are accessing healthcare. The aim of this study was to examine the impact of COVID-19 on emergency department (ED) attendance for frequent attenders and to explore potential reasons for changes in attendance. Design: This convergent parallel mixed methods study comprised two parts. Setting: An interrupted time-series analysis evaluated changes in ED presentation rates; interviews investigated reasons for changes for frequent ED users in a culturally and linguistically diverse setting. Participants: A total of 4868 patients were included in the time series. A subgroup of 200 patients were interviewed, mean age 66 years (range 23–99). Results: Interrupted time-series analysis from 4868 eligible participants showed an instantaneous decrease in weekly ED presentations by 36% (p<0.001), with reduction between 45% and 67% across emergency triage categories. 32% did not know they could leave home to seek care with differences seen in English versus non-English speakers (p<0.001). 35% reported postponing medical care. There was a high fear about the health system becoming overloaded (mean 4.2 (±2) on 6-point scale). Four key themes emerged influencing health-seeking behaviour: fear and/or avoidance of hospital care; use of telehealth for remote assessment; no fear or avoidance of hospital care; not leaving the house for any reason. Conclusions: This study demonstrated reduced ED use by a vulnerable population of previously frequent attenders. COVID-19 has resulted in some fear and avoidance of hospitals, but has also offered new opportunity for alternative care through telehealth.